2019
DOI: 10.1161/strokeaha.119.026864
|View full text |Cite
|
Sign up to set email alerts
|

Headache Outcomes After Treatment of Unruptured Intracranial Aneurysm

Abstract: Background and Purpose— While unruptured intracranial aneurysms may be discovered incidentally in the workup of chronic headache, it remains unclear whether their treatment ultimately impacts headache severity. We aim to conduct a systematic review and meta-analysis assessing headache severity after treatment of unruptured intracranial aneurysm. Methods— MEDLINE and EMBASE were systematically reviewed. Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In our case, the endovascular intervention (bilateral flow diverting stent placement) not only resolved the coital headache but also improved the patient's regular migraine. This is consistent with previous studies that demonstrated coil embolization of unruptured aneurysms resulted in a reduction of the severity of regular headaches in a majority of patients [12][13][14].…”
Section: Discussionsupporting
confidence: 93%
“…In our case, the endovascular intervention (bilateral flow diverting stent placement) not only resolved the coital headache but also improved the patient's regular migraine. This is consistent with previous studies that demonstrated coil embolization of unruptured aneurysms resulted in a reduction of the severity of regular headaches in a majority of patients [12][13][14].…”
Section: Discussionsupporting
confidence: 93%
“…For example, a "sentinel headache" is well-described in the literature and is thought to be associated with local thrombosis (12). Chronic headaches may have variable presentations but most frequently resemble migraines (13). In 2013, Lebedeva et al ( 14) conducted a prospective case-control study of 199 patients and found that migraine-like headaches without aura were significantly associated with saccular aneurysms up to 1 year before rupture (odds ratio [OR], 6.7; 95% confidence interval [CI], 3.8-11.9; p ≤ 0.001).…”
Section: Discussionmentioning
confidence: 99%